EMPOWERING VILLAGE POULTRY FARMERS' FAMILIES THROUGH TRAINING IN THE MANUFACTURING OF CLOCK MACHINE BASED HATCHING MACHINES - Tarmizi; Maimun (CV. Naskah Aceh, 2022)
The aim of the PKM program is to empower village poultry farming families through training in making clockwork-based incubators. It is hoped that this will be able to open up the community's mindset for making breeding poultry. Make it easier for people to hatch chicken and duck eggs so that it becomes more efficient, effective and economical. Community Service will be held from 9 to 11 June 2022 in Kajhu Village, Baitussalam District, Aceh Besar Regency. The method for implementing the PKM program is in the form of counseling, training on techniques for making hatching machines that are designed to be automatic, effective and efficient. The hatching machine is designed to be self-assembled so that breeders can determine how many eggs will be hatched in one period. The hatching machine can hatch 100 eggs with 75% success. The 25% that don't hatch is probably because not all the eggs put in the hatching machine are fertile. Kajhu Village has great potential for developing duck breeding. The group's enthusiasm can be seen from the spirit of mutual cooperation in making hatching machines and the large number of participants who attended the PKM activities. The large amount of agricultural waste such as bran can support it as a source of animal feed. Empty, useless land can be planted with companion plants to be used as animal feed.